Analisis Lagu “Perayaan Mati Rasa” Oleh Umay Shahab Menggunakan Pendekatan Ekspresif - Azrikul Muna (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
The song "Numbing Celebration" by Umay Shahab takes an expressive approach. This research uses a qualitative descriptive method with the main data in the form of song lyrics. The analysis focuses on the author's expression of feelings and experiences in the song. The song "Numb Celebration" describes the feelings of someone who experiences disappointment and hurt in life, so they feel numb. The song's lyrics express emptiness and sadness, but also contain a message about accepting reality and celebrating happy memories. This research found that the song "Natural Celebration" contains deep meaning about how humans deal with feelings of loss. Umay Shahab conveyed the message that someone's passing should not make us drown in sadness, but should be an opportunity to celebrate the beautiful memories we shared together. Through speech act analysis, this research identifies four types of speech acts in song lyrics: assertive, directive, expressive, and commissive. This analysis shows how song lyrics express feelings, provide invitations, and express the author's commitment.